THE TREATMENT OF TOXIC AND HAZARDOUS MATERIAL WASTE AT THE LANDFILL OF PT BATURONA ADIMULYA MUSI BANYUASIN REGENCY, SOUTH SUMATRA PROVINCE - Lina Rianti; Dicky Rahmansyah (Jurnal Cakrawala Ilmiah, 2022)
PT Baturona Adimulya is a holder of coal mining business license located in Keluang Selatan Village, Musi Banyuasin Regency, South Sumatera Province. In production process, there must be leftover materials or toxic and hazardous material waste which is hazardous for the environment and human’s health. Therefore, there is a treatment of toxic and hazardous material waste to treat the leftover materials from the production. Toxic and hazardous materials waste refers to leftover of an activity containing hazardous and toxic materials because the characteristics, concentration and amount could pollute the environment. The toxic and hazardous material waste treated by PT Baturona Adimulya were used filter, used dust cloth, used battery, used hose, used lamp and used oil, and those have toxic characteristics such a used filter, used dust cloth, used hose and used oil. The waste which is corrosive were used oil and hazardous for the environment was lamp. The treatment of toxic and hazardous material waste conducted by environment department were identifying the waste, collecting the waste, labeling of symbolizing the waste, storing the waste at the landfill until the waste was picked up by third party which already had special license to conduct toxic and hazardousa material waste hauling according to the applied regulations.